Narrative Styles and Institutional Isomorphism in South African CEOs’ Shareholder Letters - Du Toit, Elda; Esterhuyse, Leana (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
Among the most-read corporate documents are chief executive officers’ (CEOs’) shareholder letters. Using institutional isomorphism as lens, this study examines the extent to which the narrative styles used by South African CEOs in their shareholder letters are similar to the styles used by CEOs at leading international companies. The study also explores the degree to which impression management techniques are present in the South African CEOs’ shareholder letters. The study uses DICTION software to conduct a narrative analysis of South African CEOs’ shareholder letters for a single financial year, and compares the findings with those drawn from the Craig and Amernic (2018) study of the shareholder letters of CEOs from samples of international Fortune 500 and FTSE 100 companies. The study finds that optimism and realism are the two most-used narrative styles in South African CEOs’ shareholder letters, and that these findings are markedly similar to those generated by the Craig and Amernic (2018) study of international companies. The study contributes to the understanding of normative institutional isomorphism in corporate reporting by providing empirical evidence that the narrative styles employed by CEOs of companies in a developing economy with high corporate governance standards conform to the same norms as those of CEOs of large international companies. The study also finds that the South African CEOs’ dominant communication styles in the shareholder letters lend themselves to being tools of impression management.
Keywords: corporate communications, narrative styles, CEO shareholder letters, institutional isomorphism, South Africa